Influence of hot water treatment on nutritional quality attributes of cold stored apple (Malus × domestica) - SINGH, AJIT KUMAR; SETHI, SHRUTI; ASREY, RAM; KUMAR, RAJU (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out at ICAR-Indian Agricultural Research Institute, New Delhi during 2021–2023 to study the effect of postharvest hot water treatment (HWT) on the nutritional quality attributes of apple [Malus × domestica Borkh.] cv. Royal Delicious. Apple fruits were exposed to hot water at 48, 50, 52 and 54°C for 2, 3, 4 and 5 min. Following the treatment, the fruits were cold stored (2±1°C, 90–95% relative humidity) for 90 days and evaluated for quality changes at every 15 days interval. Our results revealed that HWT of apple fruits at 48°C and 50°C were best for optimum retention of nutritional quality of apple fruits. Exposure of fruits to HWT at 48°C/5 min and 50°C/2 min resulted in least (0.73%, 0.75%) loss of ascorbic acid and anthocyanin content (0.10%, 0.21%), respectively as compared to other temperature-time combinations. At the end of a three month storage period, under control treatment, fruits exhibited 9.56% reduction of antioxidant (AOX) activity in comparison to 0.17–2.21% reduction in HWT apples. The maximum loss in quality attributes was noticed at highest temperature-time exposure (54°C/5 min). Thus, it was observed that the right combination of temperature and time for HWT is crucial to maintain fruit quality attributes without compromising nutritional value.